Characteristics and applications of size-segregated biomass burning tracers in China's Pearl River Delta region. (February 2015) - Zhang, Zhisheng; Gao, Jian; Engling, Guenter; Tao, Jun; Chai, Fahe; Zhang, Leiming; Zhang, Renjian; Sang, Xuefang; Chan, Chuen-yu; Lin, Zejian; Cao, Junji
Abstract: Biomass burning activities in China are ubiquitous and the resulting smoke emissions may pose considerable threats to human health and the environment. In the present study, size-segregated biomass burning tracers, including anhydrosugars (levoglucosan (LG) and mannosan (MN)) and non-sea-salt potassium (nss-K + ), were determined at an urban and a suburban site in the Pearl River Delta (PRD) region. The size distributions of biomass burning tracers were generally characterized by a unimodal pattern peaking in the particle size range of 0.44–1.0 μm, except for MN during the wet season, for which a bimodal pattern (one in fine and one in coarse mode) was observed. These observed biomass burning tracers in the PRD region shifted towards larger particle sizes compared to the typical size distributions of fresh biomass smoke particles. Elevated biomass burning tracers were observed during the dry season when biomass burning activities were intensive and meteorological conditions favored the transport of biomass smoke particles from the rural areas in the PRD and neighboring areas to the sampling sites. The fine mode biomass burning tracers significantly correlated with each other, confirming their common sources. Rather high ΔLG/ΔMN ratios were observed at both sites, indicating limited influence from softwood combustion. High Δnss-K + /ΔLG ratios further suggested that biomass burning aerosols in the PRD were predominately associated with burning of crop residues. Using a simplified receptor-oriented approach with an emission factor of 0.075 (LG/TC) obtained from several chamber studies, average contributions of biomass burning emissions to total carbon in fine particles were estimated to be 23% and 16% at the urban and suburban site, respectively, during the dry season. In contrast, the relative contributions to total carbon were lower than 8% at both sites during the wet season. Highlights: First report of size distributions of biomass burning tracers in the PRD. Origins of biomass burning aerosols were identified using multiple tracer method. Biomass smoke contributed significantly to ambient aerosol in the PRD region.